Motivation for Learning Chinese as a Second Language: A Case Study of Students at Thu Dau Mot University - Hoang, Quoc (Technium Social Sciences Journal, 2024)
This study investigated the motivation of Chinese language learners by surveying over 138 students from various majors who are studying Chinese as a foreign language at the Foreign Language Center of Thu Dau Mot University. The results showed that students have a relatively positive learning motivation. In terms of the relationship between achievement and learning motivation, the motivation to fulfil the university's foreign language requirements accounted for the highest proportion (81.7%). This was followed by the motivation to find a job easily (66.7%), as they believe this is an essential condition that determines the material results of their work after graduation. The motivation to have the opportunity to advance in their careers later on is also relatively high (accounting for 62.7%). The motivation to learn Chinese to listen to music, watch movies in Chinese, the motivation to learn because of interest in Chinese music and cinema (49.2%), and a liking for Chinese history and culture (33.3%) are factors that affect students’ academic performance.